Evaluation of the presence and general characterization of canalis sinuosus based on cone-beam computed tomography images: a literature review - Smala, Kamila; Miazek, Weronika; Moskwa, Maria; Różyło-Kalinowska, Ingrid; Futyma-Gąbka, Karolina; Piskórz, Magdalena (Journal of Stomatology, 2023)
Canalis sinuosus (CS) is a small branch of infra-orbital canal that contains anatomical structures of clinical significance in dentist’s daily practice. Accurate identification of CS and its branches is crucial for reducing complications in dental treatments. Therefore, knowledge about CS is systematically expanding, and its importance is increasing. The aim of this study was to conduct a literature review on the prevalence, location, diameter, and trajectory variations of CS as well as the influence of age, gender, and surgical implications. A systematic review of the literature was performed. Two reviewers gathered and analyzed articles from electronic databases, including PubMed, Semantic Scholar, and Google Scholar. The frequency of CS presence was evaluated through a systematic review conducted using MedCalc, with a significance level of 5%. Due to significant heterogeneity among included papers, a random effects model was applied. Out of 276 initially identified articles, 12 studies were eventually included in the review. All were based on cone-beam computed tomography (CBCT) examinations and their results. The systematic review showed that overall prevalence of CS was 54.44%, CS presence among women was 56.76% and men 43.24%, unilateral CS was observed in 41.78%, whereas bilateral was found in 58.22% of CBCT images. CS may exhibit variability in trajectory, location, and diameter. The analyzed articles did not demonstrate statistically significant differences in age. Recent research indicates an increasing prevalence of CS, possibly due to greater observer awareness regarding its presence.